Akidah Akhlak Teacher’s Strategy in Forming Students’ Responsible Attitude - Uswatun Hasanah; Sulistia Ningrum (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper examines the Akidah Akhlak teacher's strategy, obstacles, and solutions in forming students' responsible attitudes. The research uses qualitative methods. Data collection techniques were carried out through interviews, observation, and documentation. The research results indicate that the Akidah Akhlak teacher's strategy in forming the students’ responsible attitude is providing reward and punishment, motivation, and a personal approach. Meanwhile, the Akidah Akhlak teacher's obstacles in forming students' responsible attitudes come from the student's personality, the parents who are less supportive, and the wrong association. The solutions carried out by the Akidah Akhlak teacher come from the cooperation between the teacher and the student’s parents and building intensive communication and come from the teacher who gives positive thoughts to students and puts a little positive support to students in giving assignments. This research can provide an overview and contribution to increasing the students’ responsible attitude that must always be sought by the teacher, and the importance of the parent’s role in constructing a responsible attitude of students.